A STUDY ON EMPLOYER BRANDING WITH SPECIAL REFERENCE TO HIROTEC INDIA PRIVATE LIMITED - M, Karthika; Latha, V (International Journal of Research -GRANTHAALAYAH, 2017)
Employer branding is the most recent and current trend in every organization today. Due to lack of employer branding organizations are facing lots of problems in retaining talented workforce especially in industries. The primary objective is to study on employer branding with special reference to Hirotec India Private Limited, Coimbatore. This study would help the Hirotec India Private Limited professionals to focus on the need for the development and exploration of effective Employer-Branding techniques and strategies/ interventions. In the present research, deductive research method has been followed. The field survey method was employed to collect the primary data from 219 respondents through a well framed questionnaire. The result indicated that the development value in employer branding influenced the employee’s turnover intention. The resultant framework is useful in providing a better understanding on how to improve an effective human resource management from an administrative perspective. The findings would make obtainable for the organizations’ management to improve their strategic planning to preserve their valuable employees, thus, building the human assets for the organization.